Penerapan Teknologi Formulasi Herbisida Nabati Berbahan Gulma Lokal di Kelompok Tani Bina Warga untuk Mendukung Ketahanan Pangan di Kota Tarakan: Application of Vegetable Herbicide Formulation Technology Made from Local Weeds in Community Development Farmer Groups to Support Food Security in Tarakan City - Murtilaksono, Aditya; Adiwena, Muh.; Rahmadhani, Eva; Zhafira, Dayang Nazwa; Subianti, Anita Yuli; Fatmawati, Fatmawati; Sari, Nove Kurniati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Bina Warga Farm has problems in cultivation, namely still needing to gain knowledge in organisms that disturb plants and high production costs caused by using chemical herbicides to control weeds in cultivated plants. PKM aims to apply technology to formulate plant-based herbicides from weeds and increase insight into handling organisms that disturb plants. This PKM activity was carried out at the Bina Warga Farm, Kampung 1 Village, Central Tarakan District, Tarakan City, North Kalimantan. The activities carried out by PKM are preliminary surveys, outreach, introduction and handling of the organism that disturbed the plant, production needs analysis, assistance in marketing harvests, and monitoring and evaluation of activities. As a result of PKM activities, the Bina Warga Farm was able to create plant-based herbicide formulations, increase understanding of the handling of organisms that disturbed plants, and expand sales of crops.